2017
DOI: 10.3791/54137
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting and Analyzing Male Mouse Ultrasonic Vocalization (USV) Songs

Abstract: Mice produce ultrasonic vocalizations (USVs) in a variety of social contexts throughout development and adulthood. These USVs are used for mother-pup retrieval1, juvenile interactions2, opposite and same sex interactions345, and territorial interactions6. For decades, the USVs have been used by investigators as proxies to study neuropsychiatric and developmental or behavioral disorders789, and more recently to understand mechanisms and evolution of vocal communication among vertebrates10. Within the sexual int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…However, future studies should further compare the different types of analyses and perhaps include a hand-scored analysis of the Holy and Guo taxonomy to improve understanding of the capacity of the proposed automated analysis to accurately extract data. 24 Secondly, the use of both systems may be advantageous in identifying the changes following loss of Fmr1. Previous studies have indicated that declines in body temperature can map onto increases in the number of vocalizations produced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, future studies should further compare the different types of analyses and perhaps include a hand-scored analysis of the Holy and Guo taxonomy to improve understanding of the capacity of the proposed automated analysis to accurately extract data. 24 Secondly, the use of both systems may be advantageous in identifying the changes following loss of Fmr1. Previous studies have indicated that declines in body temperature can map onto increases in the number of vocalizations produced.…”
Section: Discussionmentioning
confidence: 99%
“…24 In order to determine whether the automated method would be suitable for neonatal vocalizations, we measured syllable production, as well as acoustic and temporal properties, then compared the results to the results obtained using previously described methodology. 24 In order to determine whether the automated method would be suitable for neonatal vocalizations, we measured syllable production, as well as acoustic and temporal properties, then compared the results to the results obtained using previously described methodology.…”
Section: Matlab Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonic vocalization testing was performed to assess vocal function in mice 1 week prior to surgery and at 1, 2, and 5 WPS. Two to three nights prior to vocalization testing, mice were co-housed with a sexually mature female mouse overnight to sexually experience the male mice, as sexually experienced male mice are likely to produce greater numbers of ultrasonic calls (Chabout, Jones-Macopson, & Jarvis, 2017 (Grant et al, 2014;Grant et al, 2015;Hammerschmidt et al, 2012). Offline acoustic analysis of vocal recordings for each mouse were analyzed using SASLab Pro (Avisoft, Germany).…”
Section: Ultrasonic Vocalizationsmentioning
confidence: 99%